2019
DOI: 10.1002/mbo3.963
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial communities in the solid, liquid, dorsal, and ventral epithelium fractions of yak (Bos grunniens) rumen

Abstract: Yak (Bos grunniens) is an important and dominant livestock species in the challenging environment of the Qinghai-Tibetan Plateau. Rumen microbiota of the solid, liquid, and epithelium fractions play key roles in nutrient metabolism and contribute to host adaptation in ruminants. However, there is a little knowledge of the microbiota in these rumen fractions of yak. Therefore, we collected samples of solid, liquid, dorsal, and ventral epithelium fractions from five female yaks, then amplified bacterial 16S rRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 66 publications
(96 reference statements)
3
39
0
Order By: Relevance
“…To understand the relationship between the consumption of pastoral shrubs and rumen fermentation, we used high-throughput sequencing to investigate the response of the bacterial community in yak rumen to increased shrub coverage in the alpine meadows where these animals graze. In the present study, Firmicutes and Bacteroidetes were the most predominant bacteria phyla in the rumen of these yaks, as reported previously [2,5,56,57]. At the genus level, Prevotella 1, Rikenellaceae RC9 gut group, Ruminococcaceae (NK4A214 group, UCG-010, UCG-005 and UCG-014), Christensenellaceae R-7 group, Prevotellaceae (UCG-003 and UCG-001), Fibrobacter, Saccharofermentans, Treponema 2, Selenomonas 1, Succiniclasticum and Butyrivibrio 2 constituted both the core bacterial community and main bacteria in the rumen, which mirror previous results [2,57,58].…”
Section: Characterization Of Rumen Bacteria In Yaks Grazing In Shrubsupporting
confidence: 90%
See 1 more Smart Citation
“…To understand the relationship between the consumption of pastoral shrubs and rumen fermentation, we used high-throughput sequencing to investigate the response of the bacterial community in yak rumen to increased shrub coverage in the alpine meadows where these animals graze. In the present study, Firmicutes and Bacteroidetes were the most predominant bacteria phyla in the rumen of these yaks, as reported previously [2,5,56,57]. At the genus level, Prevotella 1, Rikenellaceae RC9 gut group, Ruminococcaceae (NK4A214 group, UCG-010, UCG-005 and UCG-014), Christensenellaceae R-7 group, Prevotellaceae (UCG-003 and UCG-001), Fibrobacter, Saccharofermentans, Treponema 2, Selenomonas 1, Succiniclasticum and Butyrivibrio 2 constituted both the core bacterial community and main bacteria in the rumen, which mirror previous results [2,57,58].…”
Section: Characterization Of Rumen Bacteria In Yaks Grazing In Shrubsupporting
confidence: 90%
“…Rumen is a complex microbial ecosystem, and rumen microorganisms play important roles in the fermentation of plant proteins and polysaccharides [ 1 , 2 ]. Bacteria account for more than 95% of the total number of rumen microorganisms, and their metabolic byproducts—such as volatile fatty acids (VFA), amino acids and microbial proteins—have a significant effect on animal health and growth [ 3 – 5 ]. Although different rumen bacterial populations have distinct metabolisms, changes in the host animal diet or grazing regime can have a major influence on rumen microbial makeup [ 2 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Twenty-ve genera were all t to the linear form with dietary NDF:starch ratio, and intriguingly, 3 out of 25 signi cantly shift genera that linearly increased according to the increasing NDF:starch ratio all belonged to the family Prevotellaceae (Prevotella 1, Prevotellaceae Ga6A1 group, and Prevotellaceae YAB2003 group). As the predominant genus in current research, Prevotella was also found to be a major genus in the rumen of ruminants in previous researches [28,29], it was typically found in the intestinal tract of humans and pigs [30], and it plays critical rules in the rumen microbial metabolism process [31]. Prevotella utilizes various plant polysaccharides [32] as a major degrader of hemicelluloses [33], and shows the potential for break down complex bers [34].…”
Section: Discussionmentioning
confidence: 78%
“…At the genus level, the present study found that the unclassified bacteria within the families Muribaculaceae and Lachnospiraceae, Christensenellaceae R7, Ruminococcaceae NK4A214, Lachnospiraceae NK3A20, Ruminococcaceae UCG 014, and Ruminococcus 2 were abundant in the solid and liquid fractions ( Table 4). These bacteria have also been observed in the solid and liquid fractions of dairy cattle (De Mulder et al, 2017;Schären et al, 2017) and yak (Ren et al, 2019). The bacteria within the family Muribaculaceae encode enzymes that degrade plant glycans (hemicellulose and pectin) and host-derived glycans; they also exhibit specificity in nitrogen utilization and harbor a specific urease (Ormerod et al, 2016;Lagkouvardos et al, 2019).…”
Section: Differences In Bacterial Community Structure Among the Solidmentioning
confidence: 99%